The relationship of income on stroke incidence in Finland and China. - Yao, Honghui; Junna, Liina; Hu, Yaoyue; Sha, Xinping; Martikainen, Pekka (European Journal of Public Health, 2023)
Background Stroke incidence has continued to increase recently in most countries. The roles of individual-level income on the incidence of overall stroke and its subtypes are still unknown, especially in low- and middle-income countries and the cross-national evidence is also limited. We explored the association between individual-level income and stroke incidence in Finland and China. Methods Changde Social Health Insurance Database (N =571 843) and Finnish population register (N =4 046 205) data were used to calculate standard stroke incidence rates, which were employed to assess the absolute incidence difference between income quintiles. Cox regression was used to compare income differences in first-ever stroke incidence. Results The highest income quintile had lower overall and subtype stroke incidence when compared to lower-income quintiles. The relative difference was more evident in hemorrhagic stroke incidence. After adjusting for age and employment status, the disparity of stroke incidence between the lowest and highest income quintiles was high among both men and women and in Finland and China. The disparity was particularly notable among men: in Finland, the hazard ratio (HR) for hemorrhagic stroke was 0.633 [95% confidence interval (95% CI) 0.576–0.696] and HR 0.572 (95% CI 0.540–0.606) for ischemic stroke. The respective figures were HR 0.452 (95% CI 0.276–0.739) and HR 0.633 (95% CI 0.406–0.708) for China. Conclusions Individual-level income is related to overall and subtype stroke incidence. Future studies should explore the causal relationship between individual-level income and stroke incidence.